Different names for srajca (’shirt’) in Slavic languages - Rusek, Zbigniew (Slavia Centralis, 2021)
This paper is devoted to the names for ’shirt’ in Slavic languages, both historical, and contemporary, their etymology, derivational relations and geography. The analysed names originate from Slavic *sraky, srakъve (Old-Church-Slavonic срачица, сракыъве), Slovenian srajca, Ukrainian, Russian сорочка; the words, documented only in Old-Slavonic (хитонъ, котыга), coming from the ancient languages; the words, the former the Proto Slavonic *gzlo (characteristic to Western Slavic); contemporary names, being an early loan-word from Latin casula (present in the majority of the Slavonic languages); the name риза, being a name for ’shirt’ only in Bulgarian (in other languages it has another meaning) and typical East-Slavonic names, such as рубашка and косоворотка ’a Russian folk shirt’.